Interparental Conflict and Power-Assertive Parenting: Attention Biases to Child Emotions as Indirect Factors. - Li, Zhi; Swerbenski, Hannah G.; Sturge-Apple, Melissa L.; Davies, Patrick T. (Journal of Child & Family Studies, 2025)
Guided by the social information processing models, this multi-method longitudinal study presents the first attempt to examine attentional processes through which interparental conflict may spillover to shape maternal and paternal parenting. Specifically, we examined whether maternal and paternal attention biases for a child's face may operate as indirect factors in the association between interparental conflict and both parents' power-assertive discipline. Data were drawn from a three-wave longitudinal study (N = 235; 55.3% female; 56.2% of children were White, 21.3% were African American, and 16.2% were identified as mixed race), and we focused on the second (Child Mean age = 3.88 years old, N = 217) and the third waves. Parents' attention biases for child emotions were measured by the dot-probe task, where we innovatively used child emotion expressions as the stimulus. For mothers, greater exposure to interparental conflicts was linked to elevated attention biases towards anger, which in turn was associated with a higher likelihood for power-assertive discipline. Follow-up analyses for power-assertive discipline across the moral and prudential domains indicated that such effect was particularly related to child transgression within the moral domain. In contrast, for fathers, we did not find significant indirect effects of attention biases for child faces that might account for spillover processes. Findings promoted the understanding of the process underlying the spillover of interparental conflict within the family system as well as maternal vs. paternal differences. Highlights: We evaluated attention biases to child emotions as potential indirect factors in the spillover of interparental conflict. Greater interparental conflict was linked to higher power-assertive discipline for mothers via angry child emotions. Effects were particularly salient when maternal discipline involved child moral transgressions. Findings highlighted processes underlying the spillover of interparental conflict and differences between parents.